MRR students self-efficacy, locus of control and reasons for overstaying in UPV Miag and Iloilo City campuses - Abaldonado, Karla Altavas; Jardino, Bernadette (2014)
This study sought to find out the profile of MRR Students and its relationship to some personality factors: self-efficacy and locus of control. The respondents were composed of 78 applicants (32 males, 46 females) within A.Y 2011-2014 and 12 interviewees (7 males, 5 females) from A.Y 2013-2014. This is a descriptive-correlational study between self-efficacy, locus of control and reasons for overstaying. This study utilized the Schwarzer General Self-efficacy scale and Rotter's Locus of Control. Data were analyzed using the Pearson Product Correlation. Analysis showed that there is no significant relationship between self-efficacy and locus of control and that all of the reasons for overstaying were non-academic.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: MRR Students -- UPV, Miagao, Iloilo; MRR Students -- UPV, Iloilo City